ON CHALLENGING POINTS OF THE FORMULATION OF RESPONSIBILITY IN THE SOVIET CIVIL LAW - H. V. Idrisov (Гуманитарные и юридические исследования)
Questions of guilt of the individual, the reasons causing his guilty behavior and also negative consequences of these processes are a subject of consideration not only within the framework of psychological and philosophical science, but in law as well. In the period of the developed Roman Law particular importance was attached to existence of guilt in actions of a person and the position according to which «without guilt there is no responsibility», the representing relevance to this day was approved as an axiom. It is no secret that the research of questions of genesis of guilt reveals the regularity consisting that it (guilt) is inseparably linked with other legal category - responsibility. The question of a concept both civil responsibility, and one of its elements - guilt, is a subject of scientiic discussions in present-day legal sources. Proceeding from this context and also impossibility within one scientific article to reflect all process of genesis, the problem categories stated above, the article studies legal aspects of responsibility and its elements created in civil law of the Soviet period. Within this work opinions of scientists concerning approaches in formulation of responsibility are given, new deinitions as a result of the legal analysis of responsibility as legal category are offered. The work represents further development of single aspects of a dissertation research of the author on the subject «Guilt as a responsibility condition in the Russian civil law».